Chirality determination in crystals. Issue 2 (11th November 2021) - Valentín‐Pérez, Ángela; Rosa, Patrick; Hillard, Elizabeth A.; Giorgi, Michel
Abstract: This tutorial review article discusses chirality determination in the solid state, both in single crystals and in crystal assemblies, with an emphasis on X‐ray diffraction. The main principles of using X‐ray diffraction to reliably determine absolute structure are summarized, and the complexity which can be encountered in chiral structures—kryptoracemates, scalemates, and inversion twinning—is illustrated with examples from our laboratories and the literature. We then address the problem of the bulk crystallization and discuss different techniques to determine chirality in a large assembly of crystal structures, with a special prominence given to an X‐ray natural circular dichroism mapping technique that we recently reported. Abstract :